Some Iterative Methods for Solving Nonconvex Bifunction Equilibrium Variational Inequalities - Muhammad Aslam Noor; Khalida Inayat Noor; Saira Zainab (Journal of Applied Mathematics)
We introduce and consider a new class of equilibrium problems and variational inequalities involving bifunction, which is called the nonconvex bifunction equilibrium variational inequality. We suggest and analyze some iterative methods for solving the nonconvex bifunction equilibrium variational inequalities using the auxiliary principle technique. We prove that the convergence of implicit method requires only monotonicity. Some special cases are also considered. Our proof of convergence is very simple. Results proved in this paper may stimulate further research in this dynamic field.